Impact of missingness on clinical trials on the effectiveness of antenatal vitamin D supplementation in gestational diabetes mellitus patients - Saha, Sumanta (Journal of Ideas in Health, 2020)
Gestational diabetes mellitus (GDM) is a vital medical complication of pregnancy in which glucose intolerance is first detected or develops during gestation. GDM is associated with adverse maternal and neonatal outcomes, and contemporarily, several clinical trials have tested their incidence in antenatal vitamin D receiving GDM patients. Considering their clinical significance, these trials' findings pertaining to the above outcomes require cautious interpretation, in terms of the risk of bias due to missingness. Any such bias in randomized controlled trials (RCT) can contaminate the results of a meta-analysis that extracts data from these RCTs.